20 years after "The ontogeny of human memory: A cognitive neuroscience perspective, " where are we?. (July 2015) - Jabès, Adeline; Nelson, Charles A
In 1995, Nelson published a paper describing a model of memory development during the first years of life. The current article seeks to provide an update on the original work published 20 years ago. Specifically, we review our current knowledge on the relation between the emergence of explicit memory functions throughout development and the maturation of associated brain regions. It is now well established that the brain regions subserving explicit memory functions (i.e. the hippocampal formation) are far from mature at birth, and exhibit important and gradual structural changes during childhood and beyond. Accordingly, explicit memory functions develop progressively. While some functions are present shortly after birth (formerly proposed as pre-explicit memory), others exhibit protracted developmental profiles during the first years of life. We examine the link between the emergence of different memory functions and the maturation of specific hippocampal circuits.